Efektivitas pendidikan kesehatan menggunakan media audiovisual terhadap perilaku personal hygiene (genitalia) remaja putri dalam mencegah keputihan - Yessy - Yulistasari; Ari Pristiana Dewi; Jumaini - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research is to know the effectiveness of health education by using audiovisual toward the hygiene behavior on adolescence to prevent the fluor albus. The method was quasy design experimental. Its conducted on SMA N 2 Pekanbaru. The sample was about 106 adolescence and devided into two groups. The first group was the controling group and the second group was the experimental group. The method was simple random samples. The measurment was questioner, it had tested by validity and realibity. The analyzing was univariate and bivariate with t-dependent test and t-independent test. The result showed the significant differences toward the change personal hygiene behavior to the experimental group after the group had given the health education using audiovisual media, by p value 0,000 < α (0,05). This research recomended to every health services in order to give health education by using audiovisual toward personal hygiene behavior to adolescence to prevent fluor albus. Keywords: Audiovisual, behavior, fluor albus, health education, personal hygiene